p53 transformation-related protein: Detection by monoclonal antibody in mouse and human cells - Dippold, Wolfgang G. (1981)
A transformation-related protein of M(r) 53,000, designated p53, has been detected in a range of neoplastic cell types of the mouse by using immunoprecipitation of [(35)S]-methionine-labeled cell extracts with mouse antiserum [DeLeo, A. B., Jay, G., Appella, E., DuBois, G. C., Law, L. W. & Old, L. J. (1979) Proc. Natl. Acad. Sci. USA 76, 2420-2424]. We have now prepared a monoclonal antibody to p53 and have used it to study the occurrence and intracellular location of p53 by indirect immunofluorescence assays. In accordance with the results of immunoprecipitation, these tests showed p53 in all 13 transformed mouse cell lines studied. In each case, p53 was found in the nucleus. No p53 was detected in normal mouse fibroblasts, 3T3 cells, bone marrow cells, thymus cells, or embryo cells. A serologically related protein was detected in the nucleus of human cells by monoclonal antibody and was found in both normal and neoplastic cultured cells. Expression of p53 in human cells correlates with the growth characteristics of the culture, high p53 levels being associated with rapid cell proliferation and low p53 levels, with cessation of cell division. Normal and malignant human cells differ, however, with regard to the effect of confluency on p53 expression. Normal kidney epithelium and fetal brain cells, which express high p53 levels during exponential growth, show a prompt decrease in p53 associated with contact inhibition of cell division. Malignant cells, on the other hand, continue to express p53 after confluency and subsequent overgrowth of the monolayers. These results suggest that p53 may be involved in the normal regulation of cell division and that malignant transformation leads to abnormalities in the control of p53 expression.